Preparation of Ginsenoside Rg3 and Protection against H2O2-Induced Oxidative Stress in Human Neuroblastoma SK-N-SH Cells - Gang Li; Xiao-xiao Zhang; Lin Lin; Xiao-ning Liu; Cheng-jun Ma; Ji Li; Chi-bo Wang (Journal of Chemistry)
The aim of this study is to evaluate the protection of ginsenoside Rg3 against oxidative stress in human neuroblastoma SK-N-SH cells. 20(R)-ginsenoside Rg3 (20(R)-Rg3) and 20(S)-ginsenoside Rg3 (20(S)-Rg3) were prepared by the method of chemical degradation and column chromatography, and the structure of the two compounds was characterized by 1H-NMR and 13C-NMR spectroscopy. MTT assay and LDH leakage assay were used to determine the cell viability and the oxidative stress cellular model was established by means of H2O2 (600 μM for 4 h). We also investigated the changes of intracellular MDA content, SOD activity, and ROS formation after the treatment of ginsenoside Rg3 for 20 h. The results indicated that both 20 (R)-Rg3 and 20 (S)-Rg3 had obvious protection against H2O2-induced oxidative stress in SK-N-SH cells. Moreover, 20(R)-Rg3 exhibited better antioxidant activity than 20(S)-Rg3 in vitro. These findings are expected to provide some implication for further research and application of ginsenoside Rg3 in neuroprotection.